The Last Cordilleran Ice Sheet in Southern Yukon Territory - Jackson, Lionel; Ward, Brent; Duk-Rodkin, Alejandra; Hughes, Owen (Géographie physique et Quaternaire, 1991)
ABSTRACTThe Cordilleran Ice Sheet in Yukon radiated from ice-divides in the Selwyn, PeIIy1 Cassiar, and eastern Coast Mountains and was contiguous with a piedmond glacier complex from the St. Elias Mountains. Expansion of glaciers in divide areas could have been underway by 29 ka BP but these did not merge to form the ice sheet until after 24 ka BP. The firn line fell to approximately 1500 m at the climax of McConnell Glaciation. Flow within the ice sheet was more analogous to a complex of merged valley glaciers than to that of extant ice sheets: topographic relief was typically equal to or exceeded ice thickness, and strongly influenced ice flow. Surface gradients on the ice sheet were fractions of a degree. Steeper ice-surface gradients occurred locally along the digitate ice margin. Retreat from the terminal moraine was initially gradual as indicated by recessional moraines within a few tens of kilometres of the terminal moraine. Small magnitude readvances occurred locally. The ice sheet eventually disappeared through regional stagnation and downwasting in response to a rise in the firn line to above the surface of the ice sheet. Regional déglaciation was complete prior to approximately 10 ka BP.